Systematic review of reversible cerebral vasoconstriction syndrome. (October 2010) - Sattar, Ahsan; Manousakis, Georgios; Jensen, Matthew B
Reversible cerebral vasoconstriction syndrome (RCVS) is a cerebrovascular disorder associated with multifocal arterial constriction and dilation. RCVS is associated with nonaneurysmal subarachnoid hemorrhage, pregnancy and exposure to certain drugs. The primary clinical manifestation is recurrent sudden-onset and severe ('thunderclap') headaches over 1–3 weeks, often accompanied by nausea, vomiting, photophobia, confusion and blurred vision. The primary diagnostic dilemma is distinguishing RCVS from primary CNS arteritis. Diagnosis requires demonstration of the characteristic 'string of beads' on cerebral angiography with resolution within 1–3 months, although many patients will initially have normal vascular imaging. Many treatments have been reported to ameliorate the headaches of RCVS, but it is unclear whether they prevent hemorrhagic or ischemic complications.